2014
DOI: 10.1186/1475-2867-14-18
|View full text |Cite
|
Sign up to set email alerts
|

The basal transcription machinery as a target for cancer therapy

Abstract: General transcription is required for the growth and survival of all living cells. However, tumor cells require extraordinary levels of transcription, including the transcription of ribosomal RNA genes by RNA polymerase I (RNPI) and mRNA by RNA polymerase II (RNPII). In fact, cancer cells have mutations that directly enhance transcription and are frequently required for cancer transformation. For example, the recent discovery that MYC enhances the transcription of the majority genes in the genome correlates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 107 publications
1
41
0
Order By: Relevance
“…We observed a vast majority of our identified circRNA candidates (86%) containing a transposable element sequence (SINE/LINE) in the flanks of backsplice forming exons (Supplementary Figure S4) that could in-part explain the presence of many low frequency circular isoforms from multi-exon genes. In addition, enhanced transcription of oncogenes and other transcription factors in cancer cells [55, 56] could lead to inefficient canonical splicing due to an accelerated polymerase activity. This may also give rise to many of the low abundance circular structures as biogenesis of circRNAs has been shown to be negatively correlated with splicing efficiency [18].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a vast majority of our identified circRNA candidates (86%) containing a transposable element sequence (SINE/LINE) in the flanks of backsplice forming exons (Supplementary Figure S4) that could in-part explain the presence of many low frequency circular isoforms from multi-exon genes. In addition, enhanced transcription of oncogenes and other transcription factors in cancer cells [55, 56] could lead to inefficient canonical splicing due to an accelerated polymerase activity. This may also give rise to many of the low abundance circular structures as biogenesis of circRNAs has been shown to be negatively correlated with splicing efficiency [18].…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 was found overexpressed in different tumor types such as acute myeloid or lymphoid leukemia (AML and ALL), malignant melanoma, and lung adenocarcinoma . Furthermore, it has been shown that transcriptional inhibition has a direct cytotoxic effect on malignant cells and thus, the basal transcription machinery is a promising druggable target to block cancer cell proliferation . From this perspective, BRD4 inhibition is an emerging relevant strategy for the treatment of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, it has been shown that transcriptional inhibition has a direct cytotoxic effect on malignant cells and thus, the basal transcription machinery is a promising druggable target to block cancer cell proliferation. 48 From this perspective, BRD4 inhibition is an emerging relevant strategy for the treatment of various cancers. JQ1, a BRD4 inhibitor, is a thieno-triazolo-1,4-diazepine that displaces BET bromodomains from chromatin through recognition pocket, preventing BRD4 reading activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that cancer cells require high levels of transcription to survive and to maintain their malignant phenotype 40. Therefore, the components of the basal transcription machinery could be considered good targets to reduce global transcription, and they might have stronger effects in cancer cells when compared with non-cancerous cells (reviewed in 39).…”
Section: Tfiih As a Target For Cancer Therapymentioning
confidence: 99%